2021
DOI: 10.1016/j.ppedcard.2021.101365
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac manifestations, treatment characteristics, and outcomes of paediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2: A systematic review

Abstract: Objective To investigate cardiac manifestations, treatment characteristics, and outcomes of paediatric inflammatory multisystem syndrome (PIMS) temporally associated with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) (PIMS-TS) Method We performed a comprehensive literature search of several databases and qualitatively synthesized findings from studies. Results Twenty-six studies were included with 1228 pooled subjects, with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 55 publications
6
15
4
Order By: Relevance
“…Pediatric reviews showed a high incidence of clinically suspected myocarditis in children presenting with multisystem inflammatory syndrome [ 70 , 71 , 72 , 73 ]. There were only a few reported pediatric cases supported by CMR findings or confirmation by biopsy or autopsy [ 50 , 74 , 75 ]. The COVID-19 pandemic has also highlighted the need for EMB and autopsy sample collection to determine the correct underlying process and possible treatment directions, when facing novel pathogens [ 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pediatric reviews showed a high incidence of clinically suspected myocarditis in children presenting with multisystem inflammatory syndrome [ 70 , 71 , 72 , 73 ]. There were only a few reported pediatric cases supported by CMR findings or confirmation by biopsy or autopsy [ 50 , 74 , 75 ]. The COVID-19 pandemic has also highlighted the need for EMB and autopsy sample collection to determine the correct underlying process and possible treatment directions, when facing novel pathogens [ 76 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common echocardiography abnormalities were reduced left ventricular (LV) function, pericardial effusion with pericarditis, myocarditis, and valvular abnormalities, which are similar to other systematic reviews. 36,38,39 Patients with impaired left ventricle function, specifically impaired LV global longitudinal strain and LV apical four-chamber peak longitudinal strain at clinical presentation, are at higher risk for developing adverse acute clinical course. Subclinical left myocardial dysfunction may persist for weeks after recovery in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…This cardiac involvement may become a long-term health issue, as shown in a previous study that only 28.3% of patients had improved LVEF after hospital discharge. 39 Reduced LVEF may manifest as left-sided heart failure, which may cause fatigue, edema, and fluid retention, leading to a significant impairment on quality of life. 41 Treatments should aim to minimize the long-term impact of PIMS-TS.…”
Section: Discussionmentioning
confidence: 99%
“…PMIS, in the other hand, affects predominantly previously healthy children, 12 although some presented comorbidities such as obesity or overweight, chronic lung disease such as asthma. 20 …”
Section: Review Of Literaturementioning
confidence: 99%
“…Majority of PMIS cases are admitted to the ICU and stayed hospitalized for a median length of 4 to 12 days; fortunately, most are discharged alive until the inflammatory markers return to normal, when they are afebrile for at least 24 hours, normotensive, well hydrated, and do not require supplementary oxygen or inotropic help to keep cardiac function. 3 , 12 , 20 , 30 , 34 The mortality rate of PMIS is low, only 2% of the infected patients died from PMIS; in the US, there have been only 36 deaths from PMIS. 23 , 26 The recommended follow-up for recovering PMIS is every 1 to 2 weeks and echocardiograms 4 to 6 weeks after discharge.…”
Section: Review Of Literaturementioning
confidence: 99%